Proposta de um middleware para monitoramento de situações de emergência em ambientes físicos ou lógicos cientes de contexto - Micheloti, Gislaine Cristina (2004)
Ubiquitous computing in which information and services are offered to users in a continuous and non-intrusive way, is widely explored for classroom, meeting rooms, tourist guides, intelligent home and also safety-critical applications: industrial, aviation, metro-train safety, patient monitoring, etc. The advances in heterogeneous visualization and information access devices, sensors and wireless networks has propelled the emergence of applications that need fine grain monitoring to prevention, combat and evaluation of emergency situations. In the first case (prevention), information is captured from sensor network in order to prevent critical conditions. In the second case (combat), it can aid with more detailed information to help decision making in the management of rescue teams (for instance, in the localization of people and objects in environments with heavy smoke and/or flames), and, in the third case (evaluation), to help auditory for insurance companies, training teams, and even people responsible for the safety of the environment being monitored. In this work, a system for Monitoring Emergency Conditions in context aware environments is considered as being a physical or logical environment with sensors across it that capture context information, which are interpreted, recorded and visualized in 3D virtual environments that mimic the real environment. This work presents a proposal for a Middleware, which is platform and programming language independent that meets functional requirements of context aware systems, such as context interpretation, localization, adaptation, etc., as well as non-functional requirements, such as: reliability, efficiency, modularity, portability, interoperability and extensibility. The middleware is specified as a set of services that interact with the application, with a sensor network and with services themselves. The interaction is achieved through a publish/subscribe mechanism based on topics in that subscriptions and notifications are issued and described in XML, and transmitted through the SOAP protocol, making the system accessible from the web. The services can be integrated and executing in a single computer, or they can be distributed across the network and even ran in nodes of a sensor network.